COVID-19 and Its Impact on Islamic Equity Mutual Funds in Indonesia - Nofrianto Nofrianto; Aprila Yutegi (IAIN Salatiga, 2022)
The Islamic equity mutual funds, initially exhibiting a relatively high average interest, experienced a significant decline in Net Asset Value (NAV) in 2020 - 2021 due to the COVID- 19 pandemic. Therefore, this study analyzed the impact of the COVID-19 pandemic on the NAV of Islamic equity mutual funds and the influence of macro and micro factors, such as inflation, exchange rate, Jakarta Islamic Index (JII) trading volume, and age of mutual funds. Data were collected from a sample of 11 companies registered with the Financial Services Authority from 2014 to 2021, using the purposive sampling technique to achieve this objective. Subsequently, the data collected were analyzed using the Panel Data Regression Method, and the Wilcoxon Signed Ranked Test. The results showed that the pandemic delayed economic activity, decreasing returns on sharia investment instruments, such as the NAV of Islamic equity mutual funds. JII, trading volume, and fund age were negatively affected compared to mutual inflation and exchange rate. This study provides information that regulators can use in formulating appropriate policies to minimize the adverse effects of Covid-19 on Islamic equity mutual funds, specifically in macroeconomic policies. Likewise, investment managers can consider internal factors when positioning Islamic equity mutual funds in the NAV